Penyedian Kotak P3K Di Perguruan Tinggi Swasta Kota Surabaya Sebagai Upaya Pencegahan Kecelakaan Kerja - Moh. Nafiis Damanhuri Thoba; Friska Ayu; Afandi Sudarmawan; Merry Sunaryo (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Implementation of Occupational Safety and Health (OSH) is one form of effort to create a safe and healthy workplace free from work accidents and work-related diseases. Accidents are unexpected and unexpected events. Unexpected. One of the controls to achieve protection is to provide first aid in an accident (P3K) quickly and precisely. The results of the initial survey through observation and hazard assessment using the JSA sheet and calculating the priority scale using the CARL method found that the most dominant hazard and potential hazard caused minor and serious injuries. Therefore the activity aims to educate workers about the provision of first aid and this data can be used as baseline data for universities to determine OSH empowerment programs. Conduct mapping to provide recommendations for the correct placement of first aid kits according to regulations. The output of this activity is to provide an overview of the appropriate location of the first aid kit to minimize the severity of a work-related accident occurs. The success of the street vendors' activities can be seen from the results of the evaluation of the post-test showing that there was an increase in understanding of first aid application knowledge from 75% to 95% percent after socialization. This shows that this socialization can be well received and understood by workers and some students who participate in the socialization. The main objective of this program is to create a college environment that is safe and ensures the safety of students, lecturers, workers, and other staff while on the move.